ПРИРОДНЫЙ РАДИОНУКЛИД 210-Рb В ДОННЫХ ОТЛОЖЕНИЯХ СЕВАСТОПОЛЬСКОЙ БУХТЫ (ЧЕРНОЕ МОРЕ) - Лазоренко, Г. Е. (Marine Ecological Journal, 2023)
The first results of natural radionuclide 210Рb concentration determination in the Sevastopol Bay (the Black Sea) bottom sediments are presented. They were ranged from 6.1 to 38.7 Бккּг-1dry weight. The highest 210Рb concentrations were found in the samples collected inside of the Southern Bay, and in the locations just after its and the Kilen Bay exits. 210Рb distribution in the Sevastopol Bay bottom sediments shows its highest concentrations in the sites of dump of the city crude waste water and sea ships standing inside of Bay. It is proposed to use 210Рb as one of a common indicator of such pollution distribution in the bottom sediments of the bays relatively closed from open sea.